Anamneza in klinični status pri otroku in mladostniku - Avčin, Tadej (Medicinski razgledi, 2007)
This paper presents the main characteristics of the clinical examination of children and adolescents and differences compared to the examination of adult patients. The medical history of children and adolescents should include data on the presenting signs and symptoms, perinatal medical history, dietary history, growth and development, completed vaccinations, prior diseases, family history and psychosocial medical history. The clinical status of children and adolescents should be evaluated according to the same basic principles as for adult patients. The order of the examination should be adjusted to the child's age and mood. In addition to knowledge about typical pathological conditions, variations in child's normal development should also be taken into account in the assessment of the clinical status, along with congenital and acquired anomalies.
Keywords: Anamneza; Medical History Taking; Health Status; Zdravstveno stanje; Physical Examination; Fizikalna preiskava; Child; Otrok; Adolescenca; Adolescence; telesni pregled; otroci; mladostniki